Students' Perspectives on Using M-Reader to Support Extensive Reading Initiatives for Non-English Majors - Alajaili, Hetham M Alfaitori; Barella, Yusawinur (Journal La Edusci, 2023)
This research aims to explore the perspectives of non-English major students on the use of M-Reader as a tool for supporting extensive reading initiatives. The study investigates the effectiveness of M-Reader in enhancing reading skills, vocabulary acquisition, and fostering a love for reading in the target language. The research also examines students' experiences, satisfaction, and challenges faced while using M-Reader. By understanding students' perspectives, the study provides valuable insights for educators and curriculum developers to optimize the use of M-Reader in supporting extensive reading initiatives for non-English majors. The study adopts a quantitative descriptive research methodology to collect data and analyse the perspectives of the students. Surveys or questionnaires were employed to gather quantitative data, enabling a systematic and structured approach to acquire information about the participants' attitudes, perceptions, and experiences concerning the usage of M-Reader. The survey instruments are designed to elicit quantitative responses, such as ratings on a Likert scale or multiple-choice questions, thus producing numerical data that can be statistically analysed. This quantitative approach empowers the researchers to identify trends, patterns, and correlations within the data, facilitating a comprehensive comprehension of the students' outlook on the effectiveness and usability of M-Reader in supporting their extensive reading programs. The findings from this research contribute to the existing knowledge on the impact and utility of digital tools like M-Reader in language learning contexts.